1-D MOC simulation software for hydraulic transients: TOPsys. (July 2018) - Yang, J B; Yang, J D
Abstract: The development of hydropower in China has entered the gold period nowadays. Numerous challenging hydropower projects have been presented to researchers and scholars. In order to adapt to this trend and the need of the nation, TOPsys, an one dimensional simulation software based on the method of characteristics (MOC) for hydraulic transients, has been developed in State Key Laboratory of Water Resources and Hydropower Engineering Science, Wuhan University recently. This software has been employed for transient flow simulations of more than thirty hydropower stations in China and overseas. The whole paper is organized as follows: first, basic mathematical theory of the software was introduced. Subsequently, several typical engineering applications, including conventional power stations and pumped storage power stations, were given for validation. Finally, the versatility as well as the expandability of this software was shown with several special engineering examples.